Data on the evolution of the Valencian manna ash forests (Valencian Community, Spain), obtained through diachronic relevees - Laguna Lumbreras, Emilio; Ferrer Gallego, Pedro Pablo; Gómez Montblanch, David Cristel; Lozano Valencia, Peio José; Meaza Rodríguez, Guillermo (Geographicalia, 2015)
Results on the monitoring of phytosociological relevees of Valencian manna ash (Fraxinus ornus L.) forest –Hedero helicis-Cytisetum patentis fraxinetosum orni– for 3 decades are shown; their abundance-dominance data where collected every 10 years –1984, 1994, 2004 and 2014– in the typus nominis site of this plant association in Malacara Mountains (Buñol, Valencia, Spain). The data analysis demonstrate the progressive global increase in species richness and mean cover, notably for the species taken as evolution indicators towards the local, climacic helm oak forest (Hedero helicis-Quercetum rotundifoliae).
Keywords: Vegetation relevee; diachronical method; manna ash forests; Spain